9.6k views
0 votes
Don't remember how to solve 3 (a-6)=6a-1 (3a-18)

User Gahrae
by
5.0k points

1 Answer

4 votes

We are given:


3(a-6)=6a-1(3a-18)

Let's simplify this equation by using the distributive property. On the left, multiply everything in the parenthesis by 3. On the right, multiply everything in the parenthesis by -1. We are then left with:


3a-18=6a-3a+18

On the right, we have like terms. Combine like terms.


3a-18=3a+18

Let's move the -18 on the left side to the right side.


3a=3a+36

Let's move the +3a on the right side to the left side. When we do that, 3a cancels out. So we are left with:


0=36

Since this statement is not true, the answer would be:

No solution

User Mehul Joisar
by
5.6k points